PEMBERIAN PAKAN KOMERSIL DENGAN PENAMBAHAN PROBIOTIK YANG MENGANDUNG Lactobacillus sp. TERHADAP KECERNAAN DAN PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Sri Ramadhana; Noor Arida Fauzana; Pahmi Ansyari (Fish Scientiae, 2019)
The purpose of this research was to determine the effect of probiotics incommercial feed on feed quality, enhance increase bactery number in gut mucose and digestibility of nile tilapia (Oreocromis niloticus) through the provision of environmental friendly probiotic feed, determine the effective doses of probiotics in feed that can support the growth fish. The research was conducted for 6 (six)months, from September 2012 until February 2013. The design used in this study was completely randomized design with 4 (four) treatments and 3 (three) replicates, were treatment A (control), B (Probiotics 3%), C (Probiotics 5%) and D (Probiotic7%).The results showed that the addition of probiotic containing Lactobacillus sp.feeding with doses of 3%, 5% and 7% were able to improve the nutritional content,protein values between 32,48%-34,19% and lower crude fiber with values between 5,04-5,70% compared with no probiotics. The addition of probiotics in feed with a percentage of 3%, 5%, and 7% can increase digestibility of nile tilapia and effectiveto increase the nile weight and length growth of nile tilapia.